A dual-targeted attack: 2-benzofuran chalcone-tamoxifen combination induces apoptosis and suppresses metastatic behavior in ER+ breast cancer? - Coskun, Demet; Aydin, Ipek; Cinar-Asa, Sibel; Coskun, Mehmet Fatih; Ari, Ferda (Elsevier, 2025)
In this study, we investigated the anticancer effects of two synthesized 2-benzofuran-substituted chalcone derivatives (2a-2b) in combination with tamoxifen (TAM) on MCF-7 estrogen receptor-positive (ER+) breast cancer cells. Cytotoxicity was evaluated using the sulforhodamine B (SRB) assay in both MCF-7 and non-tumorigenic MCF-10 A cells. The combination index (CI) was calculated to determine synergistic interactions. Apoptotic cell death was confirmed via fluorescence microscopy using Annexin-V, Hoechst 33342, and Propidium Iodide (PI) staining. The involvement of apoptosis, necroptosis, and autophagy was further assessed using Z-VAD-FMK, Necrostatin-1 (Nec-1), Necrosulfonamide (NSA), and 3-Methyladenine (3-MA) inhibitors. Functional analyses including colony formation, migration, and Matrigel invasion assays were performed. Additionally, gene expression changes in apoptosis, necroptosis, and autophagy-related markers were quantified by qRT-PCR. The combination of 2-benzofuran-chalcone compounds with TAM exhibited a synergistic cytotoxic effect on MCF-7 cells, with significantly lower IC50 values compared to monotherapies, while exerting minimal toxicity on MCF10 A cells. Fluorescence staining revealed increased apoptotic features upon combination treatment. Inhibitor assays confirmed that the cell death mechanism was predominantly caspase-dependent apoptosis, with no significant involvement of necroptosis or autophagy. The combination treatment significantly impaired clonogenic capacity, cell migration, and Matrigel invasion. Gene expression analyses showed upregulation of pro-apoptotic markers and downregulation of anti-apoptotic markers, further validating apoptotic activation. This study demonstrates that 2-benzofuran-substituted chalcone derivatives synergize with TAM to induce apoptosis and suppress proliferative and metastatic potential in ER+ breast cancer cells. These findings reveal the potential of 2-benzofuran chalcone-tamoxifen combinations as a novel therapeutic strategy to enhance antitumor efficacy in hormone-dependent breast cancers.
Keywords: Breast cancer; Chalcone; Benzofuran; Cytotoxicity; Tamoxifen